Prospect of hajj savings and investment account in Nigeria: A lesson from Tabung Haji Malaysia - Alkali, Ibrahim Ali (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2012)
The Malaysian Hajj savings and investment scheme known as (Tabung Haji) is dubbed as one of the most efficient and effective Hajj management schemes in the Muslim world. As a result of this, this study aims at evaluating the payment system of the National Hajj Commission of Nigeria (NAHCON) in light of Tabung Haji Malaysia. Although a few references are found in relation to the subject under research, none of these sources aimed at providing solutions to the well-entrenched issues of the current payment and savings schemes adopted by the NAHCON that only favours the wealthy class vis-a-vis lower and middle class. In order to do that, the research uses survey method through distribution of a hundred questionnaires to the sample selected for the research. The findings of the research show that the current payment system employed by NAHCON needs restructuring and adjustment in order to help the vast majority of the Nigerian Muslim population. Ultimately, the conclusion drawn from the findings of the research show that NAHCON should employ similar savings and investment methods to emulate Tabung Haji of Malaysia in order to help the vast majority of the Nigerian Muslim population.